Socioeconomic and demographic factors influencing dietary patterns in Aktobe: a sample of Kazakhstan’s dietary culture - Baspakova, Akmaral; Ismagulova, Elmira; Suleimenova, Roza; Yelgondina, Gulden; Mussin, Nadiar M.; Zhilisbayeva, Kulyash R.; Tamadon, Amin (Frontiers in Public Health, 2025)
BackgroundDietary patterns are shaped by a combination of cultural traditions, socioeconomic conditions, and demographic characteristics. In Kazakhstan, rapid economic growth, urbanization, and globalization are influencing food consumption behaviors, with potential implications for public health. Aktobe, the third most populous city in the country, provides a relevant urban context to examine how socioeconomic and demographic factors influence dietary choices within a culturally diverse population.ObjectiveTherefore, the aim of this study was to identify the principal dietary patterns among adults in Aktobe, Kazakhstan, using principal component analysis (PCA), and to examine the influence of socioeconomic, demographic, lifestyle, and health-related factors on adherence to these patterns.MethodsThis cross-sectional study was conducted in 2024 among 460 adults aged 18–65 years (210 women, 250 men) recruited from hospitals in Aktobe. Dietary intake was assessed using a culturally adapted food frequency questionnaire, with foods categorized into 11 groups. PCA identified dietary patterns, and negative binomial regression estimated prevalence ratios (PR) for associations between explanatory variables and dietary pattern adherence.ResultsFour dietary patterns were identified: Healthy foods (chicken, fish, green tea, dried fruits, onions), Traditional Kazakh (tea with milk, rice), Bar (processed meats, mayonnaise), and Energy-dense (refined pastries, sweets). Gender, age, and meal frequency were significant predictors. Women showed higher adherence to Healthy foods and Energy-dense patterns, while younger adults adhered less to the Traditional Kazakh pattern but more to the Bar pattern. Shorter intervals between meals and not skipping breakfast were associated with Healthy foods adherence. Oral health, absence of chronic diseases, and better functional status correlated with healthier patterns.ConclusionAdults in Aktobe exhibit both traditional and modern dietary patterns, influenced by socioeconomic, demographic, and health factors. Nutrition interventions should be gender- and age-sensitive, preserve beneficial traditional practices, and address the growing consumption of energy-dense processed foods, particularly among younger adults.